Online purchase decisions on the online buying site "Shopee" viewing from the variables of trust, easy and price - Febsri Susanti; Rahma Yosefly (Marketing Management Studies, 2021)
The development of bisinees e-commerce has changed consumer behavior of shopping habits in shopping centers are now starting switch by using online media. Online purchasing decisions are preceded by an interest in the minds of consumers to make purchases. This study aims to determine the effect of Trust, Ease and price on Purchase Decisions online at the Shopee trading site. The research population is consumers who have made purchases online on the Shopee site with the sample was 100 people. Data collection was taken using a questionnaire via Google Form. Data were analyzed using multiple linear regression analysis using the SPSS 16.00 program. The results show that Trust has a positive and significant effect on Purchasing Decisions, Ease has a positive and significant effect on Purchase Decisions, price has not significant effect on Purchase Decisions.